Marketing Strategy For Beading Crafts Products Using Social Media In Smp Negeri 2 Na Ix-X Sumberjo - Ade Sri Wahyuni; Yuniman Zebua; Hayanuddin Safri (International Journal Of Community Service, 2022)
The purpose of community service is to help knowledge and skills in making handicrafts in the form of beads and also help earn income. Although still in a small scope, the resulting product is already widely known by consumers. And so that students have the knowledge and skills in using social media to train a creative and independent business spirit. The location of this community service is at SMP NEGERI 2 Sumberjo, sub-district. Na IX-X. The target in this PKM is class IX-1 students, totaling 27 students. The method used is observation, interviews and counseling. The aims of this PKM are: 1) beaded bracelet accessories with various colors that can make the bracelet very beautiful. 2) Improve the knowledge and skills of SMP NEGERI 2 SUMBERJO students in creative and entrepreneurship subject matter. 3) Students have an interest and desire to develop a business spirit through social media and online applications. 4) can produce accessories that have selling value and students have motivation by selling online, adding pocket money and helping parents.